2018
DOI: 10.1113/jp276256
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone secretagogue receptor constitutive activity impairs voltage‐gated calcium channel‐dependent inhibitory neurotransmission in hippocampal neurons

Abstract: Growth hormone secretagogue receptor (GHSR) displays high constitutive activity, independent of its endogenous ligand, ghrelin. Unlike ghrelin-induced GHSR activity, the physiological role of GHSR constitutive activity and the mechanisms that underlie GHSR neuronal modulation remain elusive. We previously demonstrated that GHSR constitutive activity modulates presynaptic Ca 2 voltage-gated calcium channels. Here we postulate that GHSR constitutive activity-mediated modulation of Ca 2 channels could be relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 96 publications
(77 reference statements)
0
28
0
11
Order By: Relevance
“…DEGs are enriched in the 13 KEGG pathway, and some of them are related to tissue growth by regulating growth-related hormones ( Table 2). Glutamatergic synapse can develop the growth neurons and promote the construction of cortical networks by affecting the expression of Growth hormone secretagogue receptor (GHSR) [50]. The Thyroid hormone signaling pathway plays a key role in muscle formation and fat metabolism in pigs by regulating thyroid hormones [51].…”
Section: Discussionmentioning
confidence: 99%
“…DEGs are enriched in the 13 KEGG pathway, and some of them are related to tissue growth by regulating growth-related hormones ( Table 2). Glutamatergic synapse can develop the growth neurons and promote the construction of cortical networks by affecting the expression of Growth hormone secretagogue receptor (GHSR) [50]. The Thyroid hormone signaling pathway plays a key role in muscle formation and fat metabolism in pigs by regulating thyroid hormones [51].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of GPCR agonist independent activity is becoming increasingly clear ( Costa and Cotecchia, 2005 ; Meye et al, 2014 ). For instance, our laboratory has demonstrated that constitutive activity of two different GPCRs has a great impact on calcium channel function ( López Soto et al, 2015 ; Agosti et al, 2017 ; Mustafá et al, 2017 ; Martínez Damonte et al, 2018 ). For D1/D5R, there is an abundance of in vitro reports demonstrating a basal increase in Gs activity in several systems ( Plouffe et al, 2010 ; Zhang et al, 2014 ; Zhang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The G protein-coupled ghrelin receptor is expressed in the pituitary, hypothalamus, hippocampus, vasculature, and GI tract [22]. To investigate if G proteins are required for Rikkunshito-induced depolarization of pacemaker potentials, we used GDP-β-S, which can permanently inactivate G protein binding proteins [23,24].…”
Section: Involvement Of G Proteins In Rikkunshito-induced Depolarizatmentioning
confidence: 99%